An Empirical Study on Software Reuse in Small IT Companies in the Balkan Region - Imeri, Florinda; Antovski, Ljupcho (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Software reuse as a distinct field of study in software engineering has been practiced since programming began. From different surveys it is seen that software reuse is an inevitable solution that has potential to improve time â€“to-market and man power/cost trends that have been ongoing, having a significant impact on software industry.Â  It helps organize large-scale development and what is more important; it makes system building less expensive. In large companies many success stories of software reuse and use components have been quoted, with its potential for achieving good quality systems in short time scales but what about small, less structured companies, who depend on the ability to produce their product as quickly as possible, while trying to keep standards high enough to keep their customers happy and their maintenance costs low. One important issue is how to make best use of reuse at the companies of small size. In this article, we described the results of our survey at several IT companies in the region, mainly in Macedonia and Kosovo. Our aim was to evaluate issues surrounding software reuse and component-based development, from the perspective of developers involved in a software development. We wanted to explore their experience with software reuse and COTS components, to look at the possible benefits, disadvantages and contributors towards successful reuse and possibly try to increase the knowledge and understanding of CBSE.